Legal Aid Clinic On Land Law in Candipari Village Sidoarjo - Lyanthi, Merline Eva; Ambarwati , Mega Dewi; Elsina L, Rosalinda; Fardayana, Taj Bahy (Jurnal Pengabdian Mandiri, 2024)
Real Work Study Activities (KKN) is a stage that must be taken by every student, especially students majoring in Law, where this mandatory activity must be taken and is a requirement that must be completed before the final stage, namely the thesis. We took the Thematic KKN program which was held for 4 months located in Candipari Village, Porong District, Sidoarjo Regency. The distance between PT and Candipari village is approximately 35 KM. This activity will of course involve Law Faculty students, local village officials, and the Candipari village community. Some of our goals for conducting KKN in Candipari Village include socialization, education and observation (training). The results of this objective are the basis for us to create research which is outlined in service journals, mass media articles, videos and reports which are submitted to the lecturers concerned. Candipari Tourism Village is a tourist village that offers historical heritage in the form of a temple, it is said that this temple is a heritage from the Majapahit kingdom, this temple is known as Candipari. Historical heritage located in Candipari Village, Porong District, Sidoarjo Regency.